Studi Manajemen Energi Listrik di RSUD Kabupaten Klungkung - Yudiyana, I Nyoman; Kumara, I N Satya; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2019)
Electrical energy in the hospital is a very vital component, because most of the facilities, infrastructure and equipment of electrical energy sources. Fluctuations in patient visits affect energy spending in RSUD Klungkung District. From the audit, it was found that IKE RSUD Klungkung Regency is 141,38 kWh / m2 / year. Referring to the standard value of Asean Database Office 1990, the consumption of electric energy building RSUD Klungkung District including the category rather extravagant. From the observations made by the condition of base case trsebut caused because the building envelope that is still not optimal, air conditioner and lamps are used there are still using old technology and employee behavior that have not realized about the importance of energy saving.  Based on the analysis that has been described and based on the conclusions that have been obtained, it can be suggested as follows: In order to consider possible efficiency improvements to be made, building design and maintenance and operation of the building in order to consider energy conservation.